Glutathione dependence of caspase-8 activation at the death-inducing signaling complex - Hentze, Hannes; Krammer, Peter H. (The journal of biological chemistry, 2002)
Apoptosis triggered by the death receptor CD95 (APO-1 or Fas) is pivotal for the homeostasis of the immune system. We investigated differential effects of glutathione depletion on CD95-triggered apoptosis in T and B cell lines as well as the glutathione dependence of caspase-8 activation. In B lymphoblastoid SKW6.4 cells, CD95-mediated apoptosis was prevented upstream of caspase-8 activation and caspase-3-like activity after acute glutathione depletion by diethyl maleate orcis-chloro-dinitrobenzene. Immunoprecipitation of the death-inducing signaling complex (DISC) revealed that the DISC was still formed in the glutathione-depleted state. The first cleavage step of procaspase-8 activation at the DISC, however, was inhibited. Accordingly, under cell-free conditions, radiolabeled procaspase-8 was processed at the immunoprecipitated DISC only after the addition of exogenous dithiothreitol or reduced glutathione. We also observed suppression of CD95-mediated apoptosis in glutathione-depleted CEM and H9 cells. Notably, Jurkat cells still died upon CD95 engagement under this condition, displaying incomplete nuclear fragmentation and a partial switch to necrosis; this may be explained by reduced cytochromec/dATP-mediated caspase activation observed in cytosol from glutathione-depleted Jurkat cytosol. Our data indicate that the activation of caspase-8 at the DISC and hence CD95-mediated apoptosis induction shows a cell-specific requirement for intracellular glutathione.
Gesehen am 15.04.2021